ELECTRONIC DIGITAL SYSTEM FUNDAMENTALS - Patrick, Dale R.; Fardo, Stephen W.; Chandra, Vigyan, 1968-; Fardo, Brian W. (River Publishers series in electronic materials, circuits and devices., 2023)
Electronic Digital Systems Fundamentals, 2nd Edition is an introductory text that provides coverage of the various topics in the field of digital electronics. The key concepts presented in this book are discussed using a simplified approach that greatly enhances learning. The use of mathematics is kept to the very minimum and is discussed clearly through applications and illustrations. Each chapter is organized in a step-by-step progression of concepts and theory. The chapters begin with an introduction, discuss important concepts with the help of numerous illustrations, as well as examples, and conclude with summaries. The overall learning objectives of this book include: Describe the characteristics of a digital electronic system. Explain the operation of digital electronic gate circuits. Demonstrate how gate functions are achieved. Use binary, octal, and hexadecimal counting systems. Use Boolean algebra to define different logic operations. Change a logic diagram into a Boolean expression and a Boolean expression into a logic diagram. Explain how discrete components are utilized in the construction of digital integrated circuits. Discuss how counting, decoding, multiplexing, demultiplexing, and clocks function with logic devices. Change a truth table into a logic expression and a logic expression into a truth table. Identify some of the common functions of digital memory. Explain how arithmetic operations are achieved with digital circuitry. Describe the operation of microcontrollers.